Odpowiedzi

2010-02-03T18:54:16+01:00
A) całość w klamrze
6(x+y) = 10y
{
y-x = 0,5

Y=0,5+X
6(X+0,5+X)=10(0,5+X)
6X+3+6X=5+10X
12X-10X=5-3
2X=2
X=1

b) całość w klamrze
10(y+2)+3(x-5)= x-5
{
25(y + 2) + 3(x-5) = -10

10Y+20+3X-15=X-5
25Y+50+3X-15=-10

25Y+3X=-45
10Y+2X=-5-5

10Y+2X=-10/:2
25Y+3X=-45

25Y+3X=-45
5Y+X=-5

X=-5-5Y
25Y+3(-5-5Y)=-45

25Y-15-15Y=-45
X=-5-5Y

10Y=30
X=-5-5Y

Y=3
X=-5-5*3
X=-20


c) całość w klamrze

2(2x-y) + 3(x+3y) = 42
{
5(x+3y) -8(2x-y) = -32

4X-2Y+3X+9Y=42
5X+15Y-16X+8Y=-32

7X+7Y=42
-11X+23Y=-32

7(X+Y)=42/:7
-11X+23Y=-32

6-X=Y
-11X+23(6-X)=-32

6-X=Y
-11X+138-23X=-32

6-X=Y
-34X=-170

X=5
Y=6-5
Y=1



Najlepsza Odpowiedź!
2010-02-03T19:04:20+01:00
A)
6(x+y) = 10y
y-x = 0,5

6x+6y=10y
y=0,5+x

6x=-4y
y=0,5+x

6x=-4(0,5+x)
6x=-2-2x
8x=-2
x=-0,25

y=0,5+(-0,25)
y=0,25

b)
10(y+2)+3(x-5)= x-5
25(y + 2) + 3(x-5) = -10

10y+20+3x-15=x-5
25y+50+3x-15=-10

2x+10y=-10|:2
3x+25y=-45

x+5y=-5
3x+25y=-45

x=-5-5y
3(-5-5y)+25y=-45
-15-15y+25y=-45
10y=-30
y=-3

x=-5-5*(-3)
x=-5+15
x=10

c)
2(2x-y) + 3(x+3y) = 42
5(x+3y) -8(2x-y) = -32

4x-2y+3x+9y=42
5x+15y-16x+8y=-32

7x+7y=42|:7
-11x+23y=-32

x+y=6
-11x+23y=-32

y=6-x
-11x+23(6-x)=-32
-11x+138-23x=-32
-34x=-170
x=5

y=6-5
y=1
  • qb4
  • Początkujący
2010-02-03T19:08:18+01:00
A)
6(x+y)=10y
y-x=0,5

6x+6y=10y
y=0,5+x

6x=10y-6y
y=0,5+x

6x=4y
y=0,5+x

6x=4*(0,5+x)
y=0,5+x

6x=2+x
y=0,5+x

5x=2
y=0,5+x

x=0,4
y=0,5+0,4

x=0,4
y=0,9

b)
10(y+2)+3(x-5)= x-5
25(y + 2) + 3(x-5) = -10

10y+20+3x-15=x-5
25y+50+3x-15=-10

10y=x-5-3x-20+15
3x=-10-25y-50+15

10y=2x-10
3x=-25y-45

2x=10y+10
3x=-25y-45

x=5y+5
3*(5y+5)=-25y-45

x=5y+5
15y+15=-25y-45

x=5y+5
40y=-60

x=5y+5
y=1,5

y=1,5
x=5*1,5+5

x=12,5
y=1,5

Sry... tylko 2 przykłady ;]